A study to assess the clinical and functional outcome of sub-vastus approach for total knee arthroplasty - Gupta, Tarun; Nigam, Anuj; Neema, Pramod P.; Rassiwala, Murtuza (International Journal of Research in Orthopaedics, 2022)
Background: Osteoarthritis and rheumatoid arthritis affects all patients of age more than 50 years, requiring total knee replacement. There are two major approaches to total knee replacement- sub-vastus approach and medial parapatellar approach. There is no common consensus on superiority of sub-vastus approach. So, we undertook the present study to evaluate the functional and clinical outcome of total knee replacement via sub-vastus approach in terms of knee society clinical and functional scores and visual analog scale along with monitoring of range of motion in the post-operative knee in the follow up period. Methods: The present prospective and observational study was conducted in the Department of Orthopaedics, Unique Super Speciality Hospital, Indore, Madhya Pradesh for a period of 12 from June 2019-May 2020 with sample size of 30 patients undergoing total knee arthroplasty. All the patients had undergone total knee replacement via sub-vastus approach. The functional and clinical results of our study were compared with available literature. Results: The mean KFS and KCS scores showed a statistically significant improvement over a period of 12 months (p<0.05), while the mean ROM showed an improvement till 6 months (p<0.05) and then it remained stable till 12 months in comparison to 6 months (p>0.05). Conclusions: On comparing the results of sub-vastus approach with the available literature we found a significant improvement in functional and clinical outcome with a stable improvement in range of motion with very few complications.